The Gut Microbiota of Marine Fish - Egerton, Sian; Culloty, Sarah; Whooley, Jason; Stanton, Catherine; Ross, R. Paul (Frontiers in Microbiology, 2018)
The body of work relating to the gut microbiota of fish is dwarfed by that on humans and mammals. However; it is a field that has had historical interest and has grown significantly along with the expansion of the aquaculture industry and developments in microbiome research. Research is now moving quickly in this field. Much recent focus has been on nutritional manipulation and modification of the gut microbiota to meet the needs of fish farming, while trying to maintain host health and welfare. However, the diversity amongst fish means that baseline data from wild fish and a clear understanding of the role that specific gut microbiota play is still lacking. We review here the factors shaping marine fish gut microbiota and highlight gaps in the research.